"Neither age nor sex sparing": the Alvor massacre 1189, an anomaly in the Portuguese Reconquista?. Issue 2 (3rd May 2020) - Wilson, Jonathan
ABSTRACT: During summer 1189, a fleet of northern crusaders en route to the Third Crusade landed in what is today Algarve and massacred 5600 inhabitants of the Islamic town of Alvor. Mentioned only fragmentarily in contemporary sources, modern commentators have either ignored the event or passed over it as an extraneous episode, being merely one more incidence of crusader savagery. Often overlooked is that these crusaders were supported by Portuguese vessels. Considering Sancho I of Portugal, soon afterwards, with another crusader fleet, would launch a campaign to conquer the nearby Almohad regional capital, Silves, the proposition emerges that the slaughter, rather than being haphazard, formed part of a strategy. If so, viewed against the Portuguese policy of preservation of target populations, Alvor stands out as an anomaly requiring urgent explanation. Through an analysis of the De Itinere Navali, a German mariner's account of the siege of Silves, and other contemporary references, this article reveals details of Sancho I's military planning, probes aspects of the complex relationship between the Portuguese Reconquista in the latter twelfth century and the international "crusading movement, " and presents new information regarding the author of the De Itinere Navali and the origins and aptitudes of his crusader shipmates.